2010
DOI: 10.1186/1471-2474-11-31
|View full text |Cite
|
Sign up to set email alerts
|

Health beliefs before and after participation on an exercised-based rehabilitation programme for chronic knee pain: Doing is believing

Abstract: BackgroundTo explore the health beliefs, experiences, treatment and expectations of people with chronic knee pain, and investigate if, how and why these change after taking part on an integrated exercise-based rehabilitation programme - Enabling Self-management and Coping with Arthritis knee Pain through Exercise, ESCAPE-knee pain.MethodsSemi-structured interviews were conducted with people with chronic knee pain, before (n = 29) and after (n = 23) participation on the programme. Thematic analysis was used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
82
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(87 citation statements)
references
References 37 publications
5
82
0
Order By: Relevance
“…As focused upon in our previous research (21), some patients disliked taking medicines because of fears surrounding toxicity and addiction. This is a common finding in research on analgesia in OA and medicine-taking in general (20,(26)(27)(28)(29). In the present study, regardless of whether they were skeptical about using medicines, patients were reliant upon their NSAID and took it routinely.…”
Section: Discussionmentioning
confidence: 66%
“…As focused upon in our previous research (21), some patients disliked taking medicines because of fears surrounding toxicity and addiction. This is a common finding in research on analgesia in OA and medicine-taking in general (20,(26)(27)(28)(29). In the present study, regardless of whether they were skeptical about using medicines, patients were reliant upon their NSAID and took it routinely.…”
Section: Discussionmentioning
confidence: 66%
“…Although qualitative research allows for a flexible examination of individual experiences,16, 36 results cannot be generalized 25. Participants were volunteers and the interview guide was designed by the researchers, which could both influence findings 37. Fall recall may have been improved with use of a standardized fall history questionnaire.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, in a longitudinal interview study nested within a randomized controlled trial of exercise for older adults with knee pain, Hurley et al (16) found that older adults with knee problems commonly attributed their pain to wear and tear or arthritis, believed that no cure was available, and expressed concerns over the safety of exercise. Other qualitative studies have also identified a large number of barriers and facilitators to exercise adherence in individuals with arthritis (35)(36)(37).…”
Section: Discussionmentioning
confidence: 99%
“…Some qualitative studies have already suggested that individuals may hold unhelpful attitudes and beliefs about their knee problems and about the role of exercise in managing their pain, which could be a barrier to exercise and physical activity behavior (16,17). However, very few studies have described the patterns of attitudes and beliefs about exercise among older adults with knee pain at a population level, particularly within the UK.…”
Section: Introductionmentioning
confidence: 99%